(untitled) (Journal of Hama University, 2024)
The diversity of human activities and the expansion of agricultural work led to an increase in nutrient accumulation, which reached aquatic ecosystems, causing algal blooms. This highlighted the importance of the treatment of surface waters using various methods, including ultrasound technology. Water samples were collected from Soriet Lake, Lattakia during an algal bloom period. Algae were cultivated in a medium composed of commercial fertilizer (NPK 20:20:20) under natural light conditions. The dominant algae genus was identified using a light microscope, and ultrasound waves with a low frequency of 40 kHz and a power density of 0.024 W/cm³ were applied at different time intervals (0 – 80 minutes) at time intervals of 5 minutes. Changes in cell concentration were studied as a result of varying treatment times. The results indicated a decrease in Chlorophyll-a concentration, from 0.98 to 0.58 mg/l, representing a 41% reduction after exposure to ultrasound waves for 80 minutes. Based on these findings, the use of ultrasound waves appeared to be an effective method. It may avoid the use of harmful chemicals and pollution, making it an environmentally friendly alternative compared to traditional methods for algae control in aquatic ecosystems.